The Feeling of Fundamentality in Zubiri - Vargas, Esteban; Colomer, Eugenia (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The paper tries to develop the role that the feeling of fundamentality plays in Zubiri. This feeling is expressed in diverse attitudes towards the problem of God (theism, atheism, etc.). We propose that the feeling allows, in part, to direct the creation of diverse possibilities of realization through value judgments. It directs, to a certain extent, the search for these diverse attitudes. On the other hand, it allows for the experience of the sketches of these attitudes. For instance, the negative experience of a determined conception of God is conditioned not only by intellective aspects, but also sentimental ones. We give some examples of this out of some philosophers’ lives.